Possible Environmental Influence on Eyewall Expansion During the Rapid Intensification of Hurricane Helene (2006) - Qin, Nannan; Wu, Liguang (Frontiers in Earth Science, 2021)
Tropical cyclone (TC) rapid intensification (RI) is usually accompanied by a rapid eyewall contraction, followed by a slow contraction, and then a nearly steady eyewall. However, this study shows that Hurricane Helene (2006) exhibited an eyewall expansion during its 30-h RI period. The possible environmental influence on the eyewall expansion during the RI of Helene is examined. It is found that the synoptic-scale circulations led to additional low-level inflows and upper-level outflows that may play an important role in the eyewall expansion during the RI of Helene. Examination of the divergence of the absolute angular momentum flux (AAMF) associated with the environmental circulation suggests that the synoptic-scale atmospheric circulation played an important role in the eyewall expansion during the RI of Helene. In the lower and middle troposphere, the synoptic-scale cross-equatorial flow, which was enhanced by the Helene-induced wave train, led to the horizontal convergence of AAMF, while the TC-trough interaction and the related outflow in the upper troposphere resulted in the divergence of AAMF. The environment-induced low-level convergence and upper-level divergence of AAMF were superimposed on the secondary circulation of Helene and may be important to the eyewall expansion during the RI by accelerating the tangential wind outside of the eyewall. This study suggests that RI can occur with an eyewall expansion.